Community Sanitation Risk Assessment of Tanjung Raja Village: A Rural Slum Study - Indah Novita Ramadhan; Yustini Ardillah; Rafika Oktivaningrum; Laura Dwi Pratiwi (Universitas Ahmad Dahlan, 2023)
Background: Areas with high sanitation risks have the potential to transmit infectious diseases. Meanwhile, Tanjung Raja Village is an area with a high level of slums and frequent flooding, so it has the potential to have sanitation risks. This study aimed to assess sanitation risk in Tanjung Raja village. Method: This was a quantitative study using the Environmental Sanitation Risk Assessment method. The study sample was all households in Neighborhood III of Tanjung Raja Village as many as 115 respondents using Simple Random Sampling. Results: The sanitation risk assessment of Tanjung Raja Village had a scoring category in RT 5 with high-risk results (score 3) and in RT 6 with fewer risk results (score 1) and Environmental health risks obtained related to sanitation included clean water, ownership of latrines, ownership of household waste bins, and wastewater disposal facilities. Conclusion: Tanjung Raja village has the potential to have a high sanitation risk with densely populated areas and flooded areas.